2014
DOI: 10.1039/c4cp00044g
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of carbon dioxide adsorption on solid boron

Abstract: The study demonstrates these “electron deficient” boron solids can capture CO2 on their basic sites due to Lewis acid–base interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 36 publications
6
31
0
Order By: Relevance
“…Among the solid sorbent studies, nanotubes [15] and metal-organic frameworks [7] have been found to be excellent solid CO 2 sorbents at a low cost. Theoretically, boron-based nano-materials have also been predicted to be effective for CO 2 capture [14,[16][17][18]. Recent work by Sun et al reported that B 80 fullerene has great potential to capture CO 2 and can separate CO 2 from H 2 , N 2 , and CH 4 [17].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Among the solid sorbent studies, nanotubes [15] and metal-organic frameworks [7] have been found to be excellent solid CO 2 sorbents at a low cost. Theoretically, boron-based nano-materials have also been predicted to be effective for CO 2 capture [14,[16][17][18]. Recent work by Sun et al reported that B 80 fullerene has great potential to capture CO 2 and can separate CO 2 from H 2 , N 2 , and CH 4 [17].…”
Section: Introductionmentioning
confidence: 96%
“…The criteria for an ideal CO 2 sorbent are high capacity, high selectivity, fast adsorption/desorption kinetics, good mechanical properties, high hydrothermal and chemical stability, as well as low cost of synthesis [13]. Solid sorbents have shown many potential advantages, including fast adsorption kinetics and low regeneration energy compared to amine-based CO 2 capture [11,14]. Among the solid sorbent studies, nanotubes [15] and metal-organic frameworks [7] have been found to be excellent solid CO 2 sorbents at a low cost.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been used to successfully determine the interactions between some gases and boron nitride nanotubes, boron nitride nanosheets, boron carbon nanotubes, and boron nanomaterials. [45][46][47][48] The self-consistent field (SCF) procedure was used with a convergence threshold of 10 -6 au on energy and electron density. The direct inversion of the iterative subspace technique developed by Pulay is used with a subspace size 6 to speed up SCF convergence on these systems.…”
Section: Methodsmentioning
confidence: 99%
“…The big differences between these configurations and adsorption energies indicate that the negatively charged B 36 N 36 has high selectivity towards removal of N 2 from CH 4 , so B 36 N 36 can serve as a good candidate for natural gas purification. Previously we have studied N 2 capture on solid boron, and we found that the adsorption energies of N 2 on the surfaces of the solid boron, such as α-B 12 and γ-B 28 Na supporting information. The adsorption energies of the two gases on the adsorbent with neutral and 1e -states are weaker and bond distances between the gases and the adsorbent with the two states are longer at the PBE level than those of at the PBE-D level.…”
Section: Resultsmentioning
confidence: 99%
“…This calculational level has been used to successfully study adsorptions, desorption and the reaction mechanisms of some gases on boron-containing nanomaterials. 5,[25][26][27][28] The adsorption energies (E ads ) of N 2 and CH 4 on B 36 N 36 are calculated from Eq. (1): E ads = (E B36N36 + E gas ) -E B36N36-gas…”
Section: Methodsmentioning
confidence: 99%